Shared decision making between patient and GP about referrals from primary care: Does gatekeeping make a difference? - Rotar, Alexandru M.; Van Den Berg, Michael J.; Schäfer, Willemijn; Kringos, Dionne S.; Klazinga, Niek S. (PLOS ONE, 2018)
Primary care faces challenging times in many countries, mainly caused by an ageing population. The GPs’ role to match patients’ demand with medical need becomes increasingly complex with the growing multiple conditions population. Shared decision-making (SDM) is recognized as ideal to the treatment decision making process. Understanding GPs’ perception on SDM about patient referrals and whether patients’ preferences are considered, becomes increasingly important for improving health outcomes and patient satisfaction. This study aims to 1) understand whether countries vary in how GPs perceive SDM, in patients’ referral, 2) describe to what extent SDM in GPs’ referrals differ between gatekeeping and non-gatekeeping systems, and 3) identify what factors GPs consider when referring to specialists and describing how this differs between gatekeeping and non-gatekeeping systems. Data were collected between October 2011 and December 2013 in 32 countries through the QUALICOPC study (Quality and Costs of Primary Care in Europe). The first question was answered by assessing GPs’ perception on who takes the referral decision. For the second question, a multilevel logistic model was applied. For the third question we analysed the GPs’ responses on what patient logistics and need arguments they consider in the referral process. We found: 1) variation in GPs reported SDM– 90% to 35%, 2) a negative correlation between gatekeeper systems and SDM—however, some countries strongly deviate and 3) GPs in gatekeeper systems more often consider patient interests, whereas in non-gatekeeping countries the GP’s value more own experience with specialists and benchmarking information. Our findings imply that GPs in gatekeeper systems seem to be less inclined to SDM than GPs in a non-gatekeeping system. The relation between gatekeeping/non-gatekeeping and SDM is not straightforward. A more contextualized approach is needed to understand the relation between gatekeeping as a system design feature and its relation with and/or impact on SDM.